Pendidikan Akhlak: Komparasi Konsep Pendidikan Ibnu Miskawaih dan al-Ghazali - Nur Hamim (Universitas Islam Negeri Mataram, 2014)
History of Islamic ethical philosophy notes the debates and discrepancies among Muslim scholars. One of these is between Ibnu Miskawaih and al-Ghazali. While the former is known as the defender of rational thought, the latter is said to be the prime supporter of mystical tradition in Islam and is often accused of being the cause of defunct of critical Islamic thought. However, to what extent and in which context those differences occur have not been discussed sufficiently. To understand these differences clearly and to distinguish the core issues of the controversies between these two great Muslim scholars, this article aims to examine Miskawaih’s and al-Ghazali’s thoughts and analyze them in a dialogical framework. This comparative study investigates the ethical concept promoted by these two figures and focuses on other related issues, such as the basic notion of ethics, human existential structure, the eminence of morality and elements of educational ethics.